DEFORESTATION OF MANGROVE ECOSYSTEMS ON TANAKEKE ISLAND, SOUTH SULAWESI, INDONESIA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Mangroves are one of the main coastal ecosystems, if the mangrove ecosystem is damaged it will have detrimental impact on humans and the surrounding habitat. This study discusses three issues, (1) how the phenomenon of forest deforestation in the period 1972-2013 in Tanakeke, (2) how the potential for deforestation of land use cover of mangroves in the island of Tanakeke, (3) how the institutional concept that occurred on Tanakeke Island during the period 1972-2013. The data used in this study are secondary data obtained from the results of previous research. The analytical method used is quantitative and qualitative data analysis. The results of this study indicate land conversion massive mangrove ecosystem has occurred since 1972-1993 implicated in a broad decline that reached 1166.61 hectare mangrove. Whereas from 1993-2013 the area of ​​mangrove forest cover that was lost due to the conversion of mangrove land into ponds reached 32.25% within 20 years. Deforestation that occurred on Tanakeke Island resulted in a decline in the level of community welfare and environmental damage. The phenomenon of damage mangrove encourages some institutions to motivate directly involvement society Tanakeke island to form of institutional andpolicy in maintaining the continuity of the mangrove ecosystem.